Synthesis of Polystyrene Fiber Membranes Prepared by Electrospinning: Effect of AgNO3 on the Microstructure - Hanifah Setyaning Budi; Akmal Zulfi; Lia Dwi Setyaningsih; Muhammad Fahroji; Ratih Amalia; Julia Angel; Bagas Haqi Arrosyid; Gugus Handika; Kurniawan Eko Saputro; Alfian Noviyanto; Yulianto Agung Rezeki (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
Polystyrene (PS) is commonly employed in insulation, packaging, filters, and medical equipment, with recent studies exploring its potential in fiber membrane production. The electrospinning technique is discussed to synthesize PS fiber membranes with high porosity and controllable diameter. Additionally, incorporating silver nitrate into PS composite fibers is explored for enhanced functionalities such as catalytic activity, high electrical conductivity, and antibacterial activity. However, PS composite fiber membranes with silver nitrate (AgNO3) metal variations are rarely observed. This research aims to modify the microstructure of PS fiber membranes produced using electrospinning by adding silver nitrate (AgNO3) with varying concentrations. PS-Ag fiber membranes are produced using N,N-dimethylformamide (DMF) solvent, which serves as a solvent and a reducing agent for Ag. The results show that the effect of Ag affected the diameter of the PS-Ag fiber membrane, with an average diameter of around 3.67 - 6.93 micrometers. Degradation occurred in these samples at a strong broadening peak near ~1300 cm-1 until ~1600 cm-1 from the Raman results. The FTIR results show that the wavelength of ~3500 cm-1 indicated the presence of OH. The presence of OH indicates that the PS-Ag fiber membrane has the potential for water filtration application